STUDI KASUS: PENTINGNYA ASUHAN KEBIDANAN KOMPREHENSIF UNTUK MENCEGAH NYERI DAN INFEKSI PERINEUM PADA IBU POSTPARTUM - Ratna Malawat; Meilany Laisouw (Jurnal Kebidanan, 2022)
Perineal rupture is a tear that occurs in the perineum during labour. Perineal rupture occurs in almost all first deliveries and is not uncommon in subsequent deliveries. The occurrence of perineal rupture is caused by maternal factors (parity, birth spacing and baby's weight), improper delivery leadership, history of delivery. Forceps extraction, vacuum extraction, device trauma and episiotomy. Perineal rupture occurs in almost all first deliveries and is not uncommon in subsequent deliveries. This case study describes how perineal rupture occurs and its healing process in Mrs. M, a 21 year old primipara. Efforts to handle or treat perineal wounds in this case are carried out by teaching how to do proper wound care, maintaining personal hygiene and providing education to increase client knowledge. Midwifery care provided can help clients accelerate the healing of perineal wounds. Comprehensive midwifery care regarding postpartum care needs to be carried out from the time of pregnancy until later in the puerperium. Thus, the client can prevent and deal with problems that occur independently so that there are no infections or complications during the puerperium.